2019
DOI: 10.58286/23684
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the effects of detector angular misalignments and accuracy enhancement of X-ray CT dimensional measurements

Abstract: Fundamental requirements for using X-ray computed tomography (CT) systems as coordinate measuring systems (CMSs) for traceable coordinate metrology are the study of measurement accuracy and the establishment of traceability to the unit of length, the meter. Due to their complex nature, CT scanning technology and thus CT measurements are affected by multiple error sources that complexly interact in the measurement chain. The German guideline VDI/VDE 2630-part 1.2 [1] provides a detailed description of the fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Ferrucci et al observed that detector tilt had the strongest effect on sphere positioning errors, followed by detector slant, and then skew. These observations are experimentally validated by Aloisi et al [81,82]. Furthermore, Ametova et al have developed a geometrical error model that can be used to determine the effects of instrument misalignments on dimensional measurements in the reconstructed volume [83].…”
Section: Calibration Of the Instrument Length Scalementioning
confidence: 90%
“…Ferrucci et al observed that detector tilt had the strongest effect on sphere positioning errors, followed by detector slant, and then skew. These observations are experimentally validated by Aloisi et al [81,82]. Furthermore, Ametova et al have developed a geometrical error model that can be used to determine the effects of instrument misalignments on dimensional measurements in the reconstructed volume [83].…”
Section: Calibration Of the Instrument Length Scalementioning
confidence: 90%